ASPECTS OF ANTI-ICE TREATMENT OF AIRCRAFT BY AIR HANDLING COMPANIES (REVIEW) - Bahrii, Mariia; Valko, Alla; Tsymbal, Nataliia (Science-based technologies, 2024)
The development of air transport requires not only the improvement of air transport, but also the issues and procedures of ground handling. These factors affect the increase of passenger traffic in airport. The quality of ground service has a direct impact on the level of choice of air transportation by passengers. It is worth noting that the effectiveness of aviation security issues depends on the level of quality of execution and compliance with ground handling requirements. The effectiveness of ground maintenance work (preparation of an aircraft for departure) significantly depends on the existing technological processes and operational work of aviation ground machinery and airport equipment. Ground handling is carried out according to two main principles - service by airport services (service of aircraft on the apron and during parking) or by handling companies. Anti-icing is carried out both by airport services and by handling companies that have contracts for the organization of airport and ground handling. Handling companies that provide airport ground handling services can be independent or owned by an airline or air carrier. Anti-icing of aircraft is an important aspect of aviation safety and flight efficiency, especially in cold climates and winter weather conditions. Modern anti-icing solutions have been developed taking into account efficiency at low temperatures and minimizing the impact on the environment, subject to compliance with environmental regulations during ground maintenance. Such solutions may include multi-component mixtures that allow to achieve better control over the formation of ice on the surface of the aircraft. A number of scientific and practical works are dedicated to the study of issues related to the ground maintenance of aircraft, taking into account all the criteria to reduce or eliminate the risks leading to unacceptable consequences. It is worth to note that the protection of the aircraft against the formation of ice is a matter of aviation safety. Anti-icing of aircraft is an important and critical element for ensuring the safety of aircraft flight. Modern systems of anti-icing processing are divided into: air-thermal, mechanical, physical-chemical and combined. The choice of anti-icing system depends on the operating conditions of the aircraft and the climatic conditions of the area where the airport is located.